Pengaruh Etika Bisnis Islam dalam Meningkatkan Kepuasan Konsumen terhadap Produk PT Paragon Technology and Innovation - Hafidz Khan; Murwanto Sigit (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Rapid developments in the business world pose challenges and risks for business people to remain competitive and maintain company continuity. In an effort to win competition, maintain market share and capture existing markets, companies must be able to adapt their business strategies considering the ever-changing environment. High quality products or services play a key role in shaping consumer satisfaction. The higher the quality of the product or service provided, the higher the consumer satisfaction, which in turn provides profits for the company. One element that influences consumer satisfaction is business ethics. Business ethics provide incentives for consumers to form strong bonds with companies. This study aims to analyse the effect of Islamic business ethics on customer satisfaction with PT Paragon Technology and Innovation products. The research approach uses the survey method. The sample in this study were 97 consumers who have used PT Paragon Technology and Innovation products. The sampling method used is the incidental sampling method. Primary data in this study are the results of respondents' answers. The data collection method in this study used a questionnaire. Data analysis using simple regression analysis tools. The results showed that there was an effect of Islamic business ethics on customer satisfaction with PT Paragon Technology and Innovation products.